Current Progress and Scalable Approach toward the Synthesis of 2D Metal–Organic Frameworks. Issue 13 (24th March 2022) - Chen, Jeffrey E.; Yang, Zhen‐Jie; Koh, Hoong Uei; Shen, Jie; Cai, Yichen; Yamauchi, Yusuke; Yeh, Li‐Hsien; Tung, Vincent; Wu, Kevin C.‐W.
Abstract: 2D metal–organic frameworks (MOF) have demonstrated exceptional properties and advantages for applications in catalysis, membrane separation, medicine, and energy harvesting and storage systems as compared to their bulk counterpart. Despite these promises, scalable synthesis of 2D MOFs remains a frontier challenge in chemistry, which limits its potential for commercialization. This review article provides a brief overview on different 2D MOF synthetic approaches followed by recent advances toward the scalable synthesis of 2D MOFs. Abstract : The methods for scalable synthesis of different 2D metal–organic frameworks are summarized. The advantage and disadvantages of different methods are compared and discussed in the article.